IMPLEMENTASI MEMANAJEMEN KONFLIK DALAM KOMUNIKASI KELUARGA PERKOTAAN PADA ERA DIGITAL - Siti Meymunah; Minna Ahmad Karim; Ani Qotuz Zuhro’ Fitriana (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
This research focuses on how to process family communication conflicts in the digital era, especially in families living in urban areas. This study discusses matters that include communication media, causes, ways to minimize and overcome communication conflicts that occur. Not only that, this research also includes a discussion of the advantages and disadvantages of communication in the digital era, whether or not communication is effective, as well as the positive and negative impacts of communication through the media available in the digital era. The research method used is a qualitative method through interviews with 8 informants located in the city of Surabaya. This research produced findings that had almost aligned responses between one respondent and another, meaning that the respondents' responses had the same implementation in managing family communication conflicts in this digital era.